Effect of bentonite clay and polypropylene matrix on the properties of silk and glass fiber-reinforced hybrid composites. (December 2021) - Mazumder, Md RH; Numera, F; Al-Asif, A; Hasan, M
Present research investigates the effect of bentonite clay and polypropylene (PP) matrix on the properties of silk and glass fiber hybrid composites. Three types of composite were prepared with 10 wt% silk and fiber at 1:1 ratio using hot press machine. In two composites commercial and recycled PP were used as matrix, while in third composite bentonite clay was added to silk and glass-reinforced commercial PP. Mechanical (tensile, flexural, impact, and hardness) tests, water absorption test, and thermogravimetric analysis were subsequently conducted. Tensile strength, flexural modulus, and hardness decreased, whereas Young's modulus, impact strength, water absorption, and thermal stability increased with the addition of bentonite clay. On the other hand, change of matrix from commercial PP to recycled PP increased Young's modulus, flexural strength, impact strength, and thermal stability and decreased tensile strength, flexural modulus, and hardness.